Effect of roflumilast on airway remodeling in asthmatic mice exposed to or not exposed to cigarette smoke: Comparison with the effect of dexamethasone. (April 2023) - Takeda, Yukihisa; Takahashi, Maki; Fuchikami, Jun-ichi; Nakamura, Hiroyuki; Aoshiba, Kazutetsu
Abstract: Cigarette smoking constitutes a risk factor for severe asthma, which is frequently linked to remodeling of the airways. Appropriate drug treatment for smokers with asthma is uncertain because many smokers with asthma are less sensitive to glucocorticoid treatment than non-smokers with asthma. The purpose of this study was to compare the anti-airway remodeling effects of dexamethasone (Dex) and roflumilast (Rof), a selective phosphodiesterases-4 inhibitor, in smoking and non-smoking mice with asthma. BALB/c mice were sensitized with ovalbumin (OVA) and then challenged with OVA for two weeks, either with or without concurrent exposure to cigarette smoke (CS). Dex (1 mg/kg body weight), Rof (5 mg/kg body weight), or vehicle alone was given orally to the mice once daily. To assess the histopathological effects of airway remodeling, lung tissue sections were obtained. Repeated OVA challenges resulted in fibrosis, goblet cell hyperplasia, and thickening of the airway but not the smooth muscle layer. The presence of CS did not have an impact on the degree of airway remodeling brought on by repeated OVA challenges. In mice repeatedly exposed to OVA either with or without CS, Dex treatment reduced the remodeling alterations. In these mice group, the Rof Treatment had a less significant impact than the Dex treatment. Dex was still more effective than Rof at reducing airway remodeling in asthmatic smoking mice. According to the current study's findings, Dex effectively prevented airway remodeling in a two-week asthma model in mice exposed to CS or not. In contrast, we found that Rof had little to no inhibitory effect of Rof on the airway in our mouse model of asthma, whether or not it had been exposed to CS. We were unable to find solid proof to support CS-induced steroid resistance to treat airway remodeling. Highlights: In asthmatic smoking mice, corticosteroids effectively prevent airway remodeling. Roflumilast does not prevent remodeling, whether they smoke or not. In asthmatic smoking mice, corticosteroids are still effective to reduce remodeling.